SONGKET SUBHANALE WEAVING PRODUCTIVITY IN FORMING THE ECONOMIC INDEPENDENCE OF SASAK WOMEN - Baiq El Badriati; Nur Syam; Sirajul Arifin (Universitas Islam Negeri Mataram, 2021)
Research on the productivity of Songket Subhanale weaving in forming Sasak women’s Economic Independence was carried out because of the researchers’ interest in the reality of weaving culture in Sukarara, Central Lombok. Sukarara Village is one of the villages that is still sustainable in carrying out the authentic traditions of Sasak culture. One of them is the culture of weaving in the Sasak term “nyesek” which is done manually by hand and simple tools but has economic value and the output has a high selling potential. The above reality is scientifically studied through qualitative research with an ethnographic approach to obtain definite and academically accountable answers. Qualitative ethnographic research provides an opportunity to examine holistically and specifically, related to the behavior, attitudes and characters inherent in the weavers in their daily activities. The findings in this study refer to two things as formulated in the research problem formulation, namely: 1) The productivity of Muslim songket weavers in Sukarara in carrying out their profession as songket weavers, they are very productive, this is illustrated through several indicators, namely: increased results achieved, ability doing the job, morale, self-development, quality / quality, efficiency, and effectiveness. 2) The implications of work ethic and productivity on the economic independence of Muslim songket weavers in Sukarara have been realized through several indicators, namely: working capitalists, breadwinners/family breadwinners, having confidence in business, able to manage finances, mentally prepared for financial disturbances, creative and initiative , and partners/husbands in synergy by prioritizing mutual respect between each other and having a commitment to complement each other.